2015
DOI: 10.1088/0004-637x/808/2/160
|View full text |Cite
|
Sign up to set email alerts
|

PHYSICAL PROPERTIES OF A PILOT SAMPLE OF SPECTROSCOPIC CLOSE PAIR GALAXIES ATz∼ 2

Abstract: We use Hubble Space Telescope Wide-field Camera 3 rest-frame optical imaging to select a pilot sample of starforming galaxies in the redshift range z = 2.00-2.65 whose multi-component morphologies are consistent with expectations for major mergers. We follow up this sample of major merger candidates with Keck/NIRSPEC longslit spectroscopy obtained in excellent seeing conditions (FWHM ∼0.5 arcsec) to obtain Hα-based redshifts of each of the morphological components in order to distinguish spectroscopic pairs fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
2
5
0
Order By: Relevance
“…In Law et al (2012b), we found that the apparent pair fraction (i.e., the number of systems whose rest-optical morphologies show a companion within 2″ of uncertain physical association) for z∼2 star-forming galaxies was 23 6 7 -+ %, consistent with the 33% observed here. Similarly, in Law et al (2015), we demonstrated using deep spectroscopic observations that ∼50% of such apparent pairs in the galaxy sample had spectroscopic redshifts consistent with physical association. We would therefore expect 1.5 genuine spectroscopic pairs in our sample of 12 AGNs, consistent with the two such systems observed.…”
Section: Morphologysupporting
confidence: 68%
“…In Law et al (2012b), we found that the apparent pair fraction (i.e., the number of systems whose rest-optical morphologies show a companion within 2″ of uncertain physical association) for z∼2 star-forming galaxies was 23 6 7 -+ %, consistent with the 33% observed here. Similarly, in Law et al (2015), we demonstrated using deep spectroscopic observations that ∼50% of such apparent pairs in the galaxy sample had spectroscopic redshifts consistent with physical association. We would therefore expect 1.5 genuine spectroscopic pairs in our sample of 12 AGNs, consistent with the two such systems observed.…”
Section: Morphologysupporting
confidence: 68%
“…Our thick disk (which does not have arms, nor do other thick disks (they are nearly but not quite ubiquitous) formed 11-12 Gyrs ago, at z = 2 − 2.5 equivalent time, which is very close to the peak of the star formation rate for the local universe as a whole (Madau and Dickinson 2014) and probably also for the Milky Way (though we expect to know more about this topic when the Gaia data are fully in and analyzed), but it is likely that the Milky Way spiral pattern requires more than one mechanism. The oldest spiral reported so far (in a sea of dwarf irregular structures imaged by HST in its deep field) is labeled as Q2343-BX442 (Law et al 2015) and is of the "companion driven" variety, being seen at a redshift that corresponds to an age near 11 Gyrs, and evolution tends to move galaxies from flocculent to grand design (Francis and Anderson 2009).…”
Section: Galactic Physicsmentioning
confidence: 99%
“…The uncertainties in the merger rate measurement at z ≥ 1 are caused by various factors, including sample selection, pair morphology and merging timescales (e.g. Law et al 2015;López-Sanjuan et al 2015;Snyder et al 2017;Mantha et al 2018;Duncan et al 2019). At z > 0.5, pair identification becomes more difficult, mostly related to the increasing uncertainties in photometric redshifts and declining resolution for morphology identifications.…”
Section: Introductionmentioning
confidence: 99%
“…False pair identification is high (>50%) from morphological identification alone, due to chance sky alignments (e.g. Patton & Atfield 2008;Chou et al 2012;Law et al 2012Law et al , 2015. Groundbased spectroscopy is only available for small samples (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation